The Effectiveness of Instagram Account @environment in Fulfilling Climate Change Information Needs in Indonesia - Diva Inggar Sabilillah; Sayyidah Afifah (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2024)
Every individual requires information daily, which is essential for decision-making and managing daily activities. Climate change has become a widely discussed topic due to its detrimental effects on the Earth, including deforestation, air pollution, water pollution, and global warming. Human activities, such as the use of fossil fuels and deforestation, play a significant role in accelerating climate change. Studies indicate that people in Indonesia are increasingly aware of climate change, though their understanding remains limited. Social media platforms, particularly Instagram, have emerged as vital tools for disseminating information about climate change. This study aims to evaluate the effectiveness of content from the Instagram account @environment in fulfilling the information needs of its followers in Indonesia regarding climate change. Grounded in concepts of communication effectiveness and climate change, the study adopts a descriptive quantitative approach within a positivist paradigm. The sample comprises 400 respondents who follow the @environment Instagram account in Indonesia. Data was gathered using a Google Form and analyzed using SPSS. The results of the descriptive statistical analysis indicate that the content shared by the Instagram account @environment is effective. Respondents find the content useful, reliable, and engaging. A simple linear regression analysis reveals that the effectiveness of social media content significantly influences the fulfillment of followers' information needs.